Nanoparticle-Assisted Sonosensitizers and Their Biomedical Applications - Zhao P (Dove Medical Press, 2021)
Pengxuan Zhao,1 Youbin Deng,1 Guangya Xiang,2 Yani Liu1 1Department of Medical Ultrasound, Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, 430030, People’s Republic of China; 2School of Pharmacy, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, 430030, People’s Republic of ChinaCorrespondence: Guangya XiangSchool of Pharmacy, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, 430030, People’s Republic of ChinaEmail youjiti@mails.tjmu.edu.cnYani LiuDepartment of Medical Ultrasound, Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, 430030, People’s Republic of ChinaEmail yani.liu@tjh.tjmu.edu.cnAbstract: As a non-invasive strategy, sonodynamic therapy (SDT) which utilizes sonosensitizers to generate reactive oxygen species (ROS) has received significant interest over recent years due to its ability to break depth barrier. However, intrinsic limitations of traditional sonosensitizers hinder the widespread application of SDT. With the development of nanotechnology, various nanoparticles (NPs) have been designed and used to assist sonosensitizers for SDT. This review first summarizes the possible mechanisms of SDT, then classifies the NPs-assisted sonosensitizers and discusses their biomedical applications in ultrasonography, drug delivery, high intensity focused ultrasound and SDT-based combination treatment. Finally, some challenges and future perspectives of NPs-assisted SDT has also been discussed.Keywords: sonodynamic therapy, sonosensitizers, nanoparticles, combination therapy